(3aJM GdbOhS aj TQM NWHI GdbGehSs - (3CHh GdYHGS CMeO Hf YHO GdYRjR Hf QTjO GdSLdeGSis; (3GdgdGdj , CHh GdYHGS CMeO Hf YHO GdYRjR Hf GdQTjO GdgdGdj GdSLdeGSj,J (B1175 (3g` s ((3GdeUWai Hf YHjO GdeNJGQ GdedbH HLjI Hf ChHc s)
(3ChdgG (B:s
(3GdMeO ddg LGYd dZI GdYQH GdYQHGA CLed GddZGJ CeG HYO , ajbhd Efi deG QCjJ cJGH GdbGehS jLQi ef cJH GddZI eLQi GdZQI ef GdGOge hCdajJ NWHJg eMbhbI Cf JSei hMOgG bGehSkG s
(3BNQgG (B:s
(3hjCJi GdJhcd HeYfi GdJcad MOjK GdUMjM ai GdLgGO (B: (3Jhcd def NQL ai SHjdg EdN , Ci Jcad dg HPdc gPG eG JjSQ ai TQM cdGe GdeDda Je s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV YHGQGJgG HGdMeQIs
(3fSNI eUMMI s
(3MhGagG eJbUaI GdChQGb s
(3bQf GdfSN (B:s
Keywords: (3GddZIs